Electronic Nicotine Delivery Systems and Smoking Cessation in Arkansas, 2014. (March 2017) - Ekanem, Uwemedimbuk S.; Cardenas, Victor M.; Cen, Ruiqi; Simon, Wanda; Chedjieu, Irene P.; Woodward, Morgan; Delongchamp, Robert R.; Wheeler, J. Gary
Objectives: As of October 2015, evidence needed to make a recommendation about the use of electronic nicotine delivery systems (ENDS) for smoking cessation was limited. We used the 2014 Arkansas Behavioral Risk Factor Surveillance System with additional state-specific questions to determine the prevalence of ENDS use, the impact of ENDS use on smoking cessation, and beliefs about ENDS use in Arkansas. Our objectives were to determine if (1) ENDS use was associated with lower odds of quitting smoking, (2) ENDS users believed that ENDS use was not harmful to their health, and (3) ENDS users believed that switching to ENDS reduced their tobacco-related health risks. Methods: We conducted a cross-sectional study of 4465 respondents to the Arkansas Behavioral Risk Factor Surveillance System and used weighted analyses to account for the complex survey design. We used a subset of records formed by (1) formers smokers who quitted smoking in the last 5 years and (2) current smokers to assess the odds of quitting. Results: In 2014, 6.1% (95% confidence interval [CI], 5.0%-7.4%) of Arkansas adults were currently using ENDS. Of the 1083 participants who were current smokers or had quit smoking within the past 5 years, 515 (54.1%) had used ENDS. Of the 515 ENDS users, 404 (80.3%) had continued smoking. ENDS use was significantly associated with reduced odds of quitting smoking (weighted odds ratio = 0.53; 95% CI, 0.34-0.83). Although 2437 of 3808 participants (62.5%) believed that it was harmful for nonsmokers to start using ENDS and 1793 of 3658 participants (47.0%) believed that switching to ENDS did not reduce tobacco-related health risks, only 80 of 165 (41.3%) and 50 of 168 (33.9%) ENDS users shared these same respective beliefs. Conclusions: Most smokers who indicated smoking in the past 5 years and who tried ENDS did not stop smoking. ENDS use was inversely associated with smoking cessation. Tobacco cessation programs should tell cigarette smokers that ENDS use may not help them quit smoking.